Intraoperative radiation therapy in the treatment of cancer: 6th International IORT Symposium and 31st San Francisco Cancer Symposium, San Francisco, Calif., September 1996 - Vaeth, Jerome M. (Frontiers of radiation therapy and oncology, 1997)
Over the past two decades, intraoperative radiotherapy (IORT) has been used for a variety of malignant tumors and has contributed significantly to improve local tumor control. Based on the 31st San Francisco Cancer Symposium and the 6th International Intraoperative Radiation Therapy Symposium in 1996, this book presents the most recent information available on the use of IORT in cancer treatment. A brief historical overview of the development of IORT is followed by discussions of its biological, physical and technical aspects. The main part of the book is devoted to the clinical applications of IORT and the results of its use in the management of cancers of the brain, head and neck, gastrointestinal tract, breast, bone, lung, urinary tract and gynecological region, and of sarcomas. A further topic considered is the quality of life of patients undergoing IORT. The findings presented indicate that IORT provides a major contribution to the control of locally advanced cancer and, in many instances, can improve long-term survival.This book is recommended reading for all clinical practitioners of oncology – surgeons, radiation oncologists and medical oncologists – as well as for radiobiologists, physicists and engineers interested in the technical development of this form of treatment
Keywords: Konferenzschrift